SCALE UP OF CYCLONE BIOREACTOR FOR THE PRODUCTION OF BIODEGRADABLE PLASTICS - Dadi Rusendi (Direktorat Sumber Daya Akademik dan Perpustakaan, 2003)
The production of microbial poly-ß-hydroxybutyrate (PHB) was studied usingcyclone bioreactors at both the 1 L lab-scale and in 75 L Pilot Plant Scale (PPS) ofPilot Plant scale. The Culture used for PHB production was Alcaligenes eutrophusDSM 545, grown on a mineral salt medium limited by the supply of nitrogen. Twodifferent carbon sources were used: standard commercial glucose and hydrolyzedpotato processing waste. The levels of dissolved oxygen obtained in the PPS werestrongly depended on the location at which the air was introduced into thereactor. However, with aeration balanced between two injection points and asimilar level of power input, 17 W/L, the PPS was able to provide at least as muchoxygen transfer capability as the lab-scale reactor. Under all condition tested, thePHB accumulation by A. eutrophus was very high, in excess of 80% of thebiomass dry weight. The potato starch was readily hydrolyzed to fermentablesugars, however, the economic feasibility of using this carbon sources requiresfurther evaluation.